Smart Contracts on the Blockchain: Design, Use Cases, and Prospects - Zacky, Mohamed Imran; Helmi, Syahri; Della Cella, Isadora (Blockchain Frontier Technology, 2023)
Since the invention of Bitcoin, blockchain technology has expanded to include more than just digital money. Because it was quickly developed and widely adopted, the blockchain allows users to perform secure transactions in an unreliable environment. One of the most critical components of real-world blockchain applications is the smart contract. In addition to being integrated into well-known blockchain-based development platforms like Ethereum and Hyperledger, smart contracts have in the digital economy and in the intelligent industries, there are a variety of potential application situations, including, among others, management, healthcare, the Internet of Things, and financial services. This paper's main objective is to present a comprehensive analysis of the research on smart contracts, including information on their inner workings, basic architecture, use cases, challenges, most recent developments, and possible future paths. Though they are still in their infancy, smart contracts have significant technical difficulties like security and privacy concerns that require more investigation. Before proposing a study of a framework based on a for smart contracts revolutionary architecture with six layers, the technique first described the workings and popular platforms of blockchain-enabled smart contracts. Second, a list of the current state of the research is provided, together with the technical and legal difficulties. In the third place, we provided several typical application examples. We talked about the several directions that smart contracts could take at the end. The purpose of this document is to serve as a useful guide and source for future research projects.